Penangkapan Karbon Dioksida Berbasis Gliserol Sebagai Solusi Berkelanjutan Untuk Mitigasi Karbon: Review - Nuryoto, Nuryoto; Ekasari, Ekasari; Agustina, Sri; Damayanti, Astrilia (Jurnal Inovasi Teknik Kimia, 2026)
Carbon dioxide (CO₂) capture technology continues to advance in line with global commitments to emission reduction. Glycerol, an abundant by-product of the biodiesel industry, has potential as an alternative absorbent due to its low cost, biodegradability, and low vapor pressure. This review aims to analyze the performance of glycerol-based CO₂ capture by evaluating the effects of temperature, pressure, gas flow rate, and solution concentration on process efficiency, as well as identifying research gaps for further development. In general, increasing operating parameters enhances the mass transfer coefficient and CO₂ capture efficiency up to an optimum limit, beyond which performance declines. The addition of solvents such as water and monoethanolamine (MEA) to glycerol has been shown to improve capture efficiency from 27.31% to 64.33%, although it may lead to the formation of by-products. Future work requires further laboratory-scale experimental studies, such as the use of bubble column reactors to enhance gas–liquid contact, in order to achieve optimal process conditions and maximize glycerol carbonate yield.